Characterization of leaf morphology of three species of Eremanthus (Vernonieae, Asteraceae): Untangling similar species - Silva, Elias Roma Da; Ribeiro, Alessandra Oliveira; Pires Lira, Marinês Ferreira (Phytotaxa, 2023)
The genus Eremanthus (Asteraceae) covers mostly arboreal species, popularly known as “candeia”. Three of these species, E. erythropappus, E. incanus and E. glomerulatus, are endemic to and extensively distributed in Brazil. “Candeias” are of commercial interest due to the good quality of their wood and, mainly, to their essential oils, used for various therapeutic purposes. These species of “candeia” have similar vegetative characteristics, mainly to E. erythropappus and E. incanus, making them difficult to differentiate in the field. This study aimed to characterize the anatomy and external morphology of these “candeia” species to facilitate identification. Qualitative and comparative analysis of the anatomy, histochemistry and ultrastructure of the leaf surface and the external morphology of the leaves were performed. The greatest differentiation between the three species was possible through the external morphological characteristics. The most representative characters were used to elaborate a dichotomous key.